ANALISIS KESESUAIAN LAHAN UNTUK KOMODITAS SAYURAN UNGGULAN DI KABUPATEN BATANG - Saksono Raharjo; - Widiatmaka; Untung Sudadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Batang Regency has potential land resource for the development of vegetable commodity because it has a diverse agro-ecological conditions, ranging from coastal areas, plains and mountains. However, these conditions have not been matched with adequate vegetable productivity because it is still below the average productivity of Central Java province. The purpose of this study were to know the primary commodities of vegetable in Batang, to know the land availability for development of primary vegetable commodities and to know available of land suitability for development of primary vegetable commodities in Batang. The analytical method used in this study were : LQ and SSA, land availability analysis and land suitability analysis.The results showed that the primary vegetables in Batang are potato, carrot, long bean, large pepper, cucumber, cayenne pepper, eggplant, cabbage and mustard. Available land for development planning based on primary vegetable horticulture area are 28.558 hectares.The results of soil analysis showed that the potential suitability classes for potatoes, cucumbers and carrots have potential level suitability of S2 and S3. Long bean,chili large, cayenne pepper, eggplant, cabbage and mustard have a potential level suitability of S1 (highly suitable) although that area were not too large. Keywords: primary commodity, land availability, land suitability